Building biosecurity for synthetic biology. Issue 7 (21st July 2020) - Trump, Benjamin D; Galaitsi, SE; Appleton, Evan; Bleijs, Diederik A; Florin, Marie‐Valentine; Gollihar, Jimmy D; Hamilton, R Alexander; Kuiken, Todd; Lentzos, Filippa; Mampuys, Ruth; Merad, Myriam; Novossiolova, Tatyana; et al.
Abstract : The fast‐paced field of synthetic biology is fundamentally changing the global biosecurity framework. Current biosecurity regulations and strategies are based on previous governance paradigms for pathogen‐oriented security, recombinant DNA research, and broader concerns related to genetically modified organisms (GMOs). Many scholarly discussions and biosecurity practitioners are therefore concerned that synthetic biology outpaces established biosafety and biosecurity measures to prevent deliberate and malicious or inadvertent and accidental misuse of synthetic biology's processes or products. This commentary proposes three strategies to improve biosecurity: Security must be treated as an investment in the future applicability of the technology; social scientists and policy makers should be engaged early in technology development and forecasting; and coordination among global stakeholders is necessary to ensure acceptable levels of risk. Abstract : Biosecurity policies and practices must be updated to accommodate the novel challenges associated with synthetic biology and to maximize technological benefits while minimizing its dual‐use potential. This Commentary proposes three strategies to improve biosecurity.